Advances in essential oils for metabolic diseases - Li, Xinxin; Tong, Min; Cao, Huilian; Sun, Xiangjuan; Zhang, Fenghua (Frontiers in Endocrinology, 2025)
Metabolic diseases are a group of complex disorders caused by abnormal metabolic processes, such as diabetes, obesity, and non-alcoholic fatty liver disease. Long-term uncontrolled metabolic diseases will significantly increase the risk of cardiovascular disease, renal damage, and neurologic complications, leading to shorter survival and reduced quality of life for patients. While conventional treatments rely on pharmacological interventions, essential oils have shown significant therapeutic potential as a natural treatment modality. Essential Oils are concentrated aromatic substances extracted from plants, possessing multiple biological activities, including antioxidant, anti-inflammatory, and insulin sensitivity modulation. Studies have shown that specific essential oil components can improve metabolic disorders, enhance insulin sensitivity, and lower blood glucose, and blood lipids through a variety of mechanisms, thus playing an active role in the management of metabolic diseases. This review highlights the therapeutic potential of EOs in managing various metabolic disorders by modulating key metabolic pathways, mitigating oxidative damage, and regulating gut microbiota. We focus particularly on the rationale for selecting EOs as a research focus—their complex chemical composition enables synergistic actions against multiple pathological targets simultaneously. Additionally, we address safety profiles and current clinical evidence supporting their translational application.